PENGARUH KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU VANDALISME SISWA KELAS VIII SMP NEGERI 1 DEMAK - Josephin Gabriella Krisnanta; Yari Dwikurnaningsih; Tritjahjo Danny Soesilo (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the significance of the influence of peer conformity on vandalism behavior in class VIII students of SMP N 1 Demak. Samples were taken using the technique proportional random sampling, so that 175 students were taken from the total population of 320 students. The research data was collected using a questionnaire technique that described 22 peer conformity items and 28 vandalism behavior items with 4 alternative answers. Analysis of the research data used a simple linear regression technique with the help of an applicationIBM Statistics SPSS 23. The results of the study showed that there was an influence of peer conformity on vandalism behavior in class VIII students of SMP Negeri 1 Demak. These results are supported by the finding of an Fcount value of 31.949 with a Sig. of 0.000b < 0.05 and t_count is 5.612 > t_table (5.612 > 1.653). The R Square value obtained is 0.154. This means that peer conformity contributes 15.4% to the vandalism behavior of class VIII students of SMP Negeri 1 Demak.